SWOT Framework of Academic Traditional Iranian Pharmacy (TIP) - Parmis Badr; Mojtaba Taghvafard (Shiraz University of Medical Sciences, 2016)
Traditional Iranian Pharmacy (TIP) is a rarity which has not been introduced to the world. In fact, this branch of pharmacy can benefit Iranians and all people right across the world. It is a new field in Iran, on which a lot of research has not been done. In other words, this field suffers from scarcity of research. This paper tries to analyze the current situation of TIP in Iran by using the SWOT framework so as to come up with strengths, weaknesses, opportunities, and threats which are associated with this field at the moment. It is believed that this new field has a lot of potentials which can benefit the health care system substantially. Moreover, it can help the economy to a great extent if the schemes and strategies presented by TIP are taken into consideration.